Asymmetric neurogenic commitment of retinal progenitors involves Notch through the endocytic pathway - Nerli, Elisa; Rocha-Martins, Mauricio; Norden, Caren (eLife, 2020)
During brain development, progenitor cells need to balanceproliferation and differentiation in order to generate different neurons in the correct numbers and proportions. Currently, the patterns of multipotent progenitor divisions that lead to neurogenic entry and the factors that regulate them are not fully understood. We here use the zebrafish retina to address this gap, exploiting its suitability for quantitative live-imaging. We show that early neurogenic progenitors arise from asymmetric divisions. Notch regulates this asymmetry, as when inhibited, symmetric divisions producing two neurogenic progenitors occur. Surprisingly however, Notch does not act through an apicobasal activity gradient as previously suggested, but through asymmetric inheritance of Sara-positive endosomes. Further, the resulting neurogenic progenitors show cell biological features different from multipotent progenitors, raising the possibility that an intermediate progenitor state exists in the retina. Our study thus reveals new insights into the regulation of proliferative and differentiative events during central nervous system development.
Keywords: quantitative live-imaging; retinal development; fate asymmetry; Notch; Sara endosomes